2023
DOI: 10.1302/0301-620x.105b2.bjj-2022-0414.r1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing two-year postoperative femoral and tibial migration of a new and an established cementless rotating platform total knee arthroplasty

Abstract: Aims The primary aim of this study was to compare the migration of the femoral and tibial components of the cementless rotating platform Attune and Low Contact Stress (LCS) total knee arthroplasty (TKA) designs, two years postoperatively, using radiostereometric analysis (RSA) in order to assess the risk of the development of aseptic loosening. A secondary aim was to compare clinical and patient-reported outcome measures (PROMs) between the designs. Methods A total of 61 TKAs were analyzed in this randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Authors from across the Netherlands are to be applauded for reporting their trial, where they randomized patients to receive either a currently-available mobile-bearing cementless TKA, with excellent registry results, or its newer equivalent. 4 The authors undertook RSA examinations of all patients at day one, and three, six, 12, and 24 months postoperatively. The authors reported the maximal total point motion (MTPM), alongside patient-reported outcome measures (PROMs) and clinical data at six weeks, and three, six, 12, and 24 months postoperatively.…”
Section: The Attune Cementless Versus Lcs Arthroplasty At Introductionmentioning
confidence: 99%
“…Authors from across the Netherlands are to be applauded for reporting their trial, where they randomized patients to receive either a currently-available mobile-bearing cementless TKA, with excellent registry results, or its newer equivalent. 4 The authors undertook RSA examinations of all patients at day one, and three, six, 12, and 24 months postoperatively. The authors reported the maximal total point motion (MTPM), alongside patient-reported outcome measures (PROMs) and clinical data at six weeks, and three, six, 12, and 24 months postoperatively.…”
Section: The Attune Cementless Versus Lcs Arthroplasty At Introductionmentioning
confidence: 99%